Online teaching and digital technologies at primary and lower secondary school level in times of the COVID-19 pandemic in 2020: Views of teachers and principals - Jakobsdóttir, Sólveig; Gissurardóttir, Salvör; Kjartansdóttir, Skúlína Hlíf; Pétursdóttir, Svava; Hjartarson, Torfi (Menntavísindasvið Háskóla Íslands, 2021)
During the COVID-19 pandemic in 2020, an increased research focus on digital competence of teachers and learners and the development of distance and online learning and education has become vital for educational systems all over the world. In Iceland, most schools at primary and lower secondary level stayed open but with considerable restrictions in terms of social distance and number of people allowed in each location. Online teaching and learning increased substantially as a result, especially for students at lower secondary level (grades 8 to 10). Surveys were sent out in spring 2020 (survey was open April 27 to May 26) by the Educational Research Institute (ERI) at the University School of Education to start charting the effects of the COVID-19 situation on learners and schools at primary and secondary level. Researchers in this project group contributed questions, relating to the use of digital technologies and online learning, to surveys for school staff in 151 schools. The results introduced in this paper are based on the answers of 1770 staff members. Of this group, 1263 indicated that they were teachers,188 school administrators, 257 special education teachers, and 180 instructors without a teaching license (participants could check more than one role). The majority of all participant groups (61–70%) thought that the schools were very well (25–32%) or rather well (36–39%) equipped with digital technologies. Also, the majority (65–70%) thought the staff was very well (15–27%) or rather well (38–53%) prepared to deal with increased online communication and distance education. Furthermore, a majority of all groups (56–77%) thought students’ technological access was sufficient for online communication and distance learning. The results indicated a large increase regarding blended and online learning. The teachers indicated that before the pandemic, 78% of their teaching was in the schools but only 19% of the teaching was web-supported and 3% blended. Conversely, during the pandemic, 30% indicated that ...